Characteristics associated with prolonged work absenteeism due to medical reasons among agribusiness workers in Peru: A cross-sectional study - Aguirre Quispe, Wilfor (2018)
Objective: To describe and analyze the factors associated with prolonged work absenteeism due to medical reasons among agribusiness workers. Materials and methods: A secondary source research was conducted in a population of 3,150 agribusiness workers in Peru. A sample of 9,443 cases of work absenteeism was taken during the years 2012 and 2013. Long-term work absenteeism was defined as ≥ 10 days. Analyzed factors were: age, sex, job tenure, type of activity, work schedule, job stability, type of contingency, and affected body system according to the diagnosis. A descriptive and multivariate statistical analysis was applied by binary logistic regression. Results: The factors explaining prolonged work absenteeism were occupational accidents (OR: 13.9, CI: 11.2- 17.2), atypical schedule (OR: 3.14, CI: 1.58-6.25), shorter job tenure (OR: 0.95, CI: 0.95-0.96), moderate-intense work activity (OR: 8.96, CI: 4.53-17.2), and lower job stability (OR: 0.64; CI: 0.54-0.77). Conclusions: Job tenure (> 15 years), atypical work schedule, moderate-intense physical activity, occupational accidents, and an unstable job contract predict prolonged work absenteeism with high certainty. Sex, age and the affected body system were not predictive of prolonged work absenteeism, but showed significant differences in the bivariate analysis.